(3efGgL GdHMK GdYdej aj Ydhe GdEYdGe (B:s (3GdWHYI GdKGfjI (B/s - (3Hf eQSdj, CMeOs ((3GdLRGFQ (B:s (3OjhGf GdeWHhYGJ GdLGeYjI ,s, 2005)
(3GdaUd GdChd (B: (3GdHMK GdYdej aj GdEYdGe h GdEJUGd GdaUd GdKGfj (B: (3GdNWhGJ GdCSGSjI dEfLGR GdHMK GdaUd GdKGdK (B: (3JfXje GdeJf GdaUd GdQGHY (B: (3GNJjGQ eaQOGJ eLJeY GdHMK GdaUd GdNGeS (B: (3COhGJ GdHMK GdYdej GdaUd GdSGOS (B: (3efGgL GdHMK aj GdEYdGe h GdEJUGd GdaUd GdSGHY (B: (3GdCSGdjH GdEMUGFjI aj CHMGK GdEYdGe h GdEJUGd Ud GdKGef GdJMdjd GdEMUGFj ddHjfGJ GdcejI GdaUd GdJGSY (B: (3GdJMdjd GdEMUGFj ddYjfGJ h GdaQhV GdYdejIs
(3HHdjhZQGajG (B: (3U(B.485497 (3edGMXI (B: (3U(B.s
Keywords: (3Ydhe GdEYdGes; (3efGgL GdHMK GdYdejs